The Effect of Live Streaming, Discounts, and Free Shipping on the Decision to Purchase Fashion Products on The Shopee Application among Students of The Solo Christian University of Technology - Clarrisa Putri Hartarin; Dewi, Adhita Maharani (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to examine the effect of Live Streaming, Discounts, and Free Shipping on Purchase Decisions of Fashion Products on the Shopee App among students of Universitas Kristen Teknologi Solo. The data used in this study was obtained from questionnaires filled out by respondents, making this a quantitative study. The researcher used Purposive Sampling, a sampling technique based on specific considerations to determine appropriate samples. A total of 40 participants were selected as the sample. Data analysis was performed using multiple linear regression. The results indicate that the variables of Live Streaming and Discounts have no significant effect on purchase decisions individually, while Free Shipping has a significant effect on purchase decisions individually. Meanwhile, the simultaneous analysis shows that the variables of Live Streaming, Discounts, and Free Shipping have an influence on purchase decisions.